The Urgency of Express Consent to Waive State Immunity in an International Commercial Arbitration Agreement: Indonesia’s Practice - Feren Thalita; Prita Amalia; Damos Dumoli Agusman (Journal of Law, Politic and Humanities, 2025)
Indonesian State-owned enterprises’ participation in the international commercial transactions have become a prime example which affects the increasing need for international commercial arbitrations today and in the future. However, the State immunity that Indonesian State-owned enterprise owns may potentially give rise to issue on the implementation of the whole arbitration process, inclusive of the recognition and enforcement of the arbitral award. This issue alone has been hotly debated from the perspective of State-owned enterprises and the foreign private parties. On that account, Indonesian State-owned enterprises are still in need of a legal solution to settle the State immunity matter, whereas express consent to waive State immunity here is in question. Through the normative and comparative juridical research, the writer has found that it is urgent for Indonesian State-owned enterprises to provide express consent to waive State immunity since, inter alia, it paves a way to prevent further procedural hindrance in the whole arbitration process. The recommendation to fortify such practice is strengthened by how solely depending on other exceptions to State immunity, which have their own complexities and uncertainties, is going to bring the parties to procedural barrier that prolong the dispute settlement itself